The Holocaust, religion, and the politics of collective memory : beyond sociology - Berger, Ronald J. 1951- (Transaction Publ, 2012)
Sociology and the Holocaust -- Why the Jews? -- The rise of Nazism and the evolution of anti-Jewish policy -- The social structure of the genocidal regime -- Jewish responses to the Holocaust -- Bystanders and third-party resistance -- European collective memories: Germany and Poland -- Jewish collective memories: Israel and the United States -- Genocide, religion, and social solidarity